Childbirth and New Mother Experiences of Arab Migrant Women. Issue 2 (March 2017) - Bawadi, Hala; Ahmad, Muayyad M.
Abstract: Purpose: To explore the experience of childbirth and becoming a new mother for Arab migrant women in the United Kingdom. Study Design & Methods: Hermeneutic phenomenology design was used to investigate the childbirth and early mothering experience of migrant Arab Muslim women from several countries to United Kingdom. Purposive sampling was chosen. Data collection was conducted through in-depth interviews. Results: The emerging theme "displacement and reformation of the self" includes four subthemes from analyses of participants' interviews. These were the emerging dominance of the nuclear family over the extended family: self-contained/self-worth; moving from dependence: self-governing/self-reliance; freedom from cultural constraints: self-determination; and achieving peace of mind: self-satisfaction. Conclusion: Exploring the perception of migrant Muslim women's childbirth and new mother experiences in a foreign land may help caregivers better understand their healthcare needs. Abstract : Arab Muslin women who have immigrated to the United Kingdom are generally pleased with the evolution of their family traditions. Without the support and advice of their extended family to guide routine decisions, they have realized freedom to conduct their lives as they wish and experienced closer relationships with their spouses. Immigration to the United Kingdom has a number of perceived positive aspects for Arab Muslim women.